Microfluidic chip development for medical application - Chong, Zhi Wei. (2013)
From inkjet printhead to micro-pneumatic systems, the field of microfluidics has been nothing short of a revolution. With advancements in the technology, micro-fluidics has also opened up a vast array of possibilities in biological applications.